A Spectrophotometric Study of Plumage Color in the Eared Dove (Zenaida auriculata), the Most Abundant South American Columbiforme - Valdez, Diego Javier (2016)
For birds, plumage color perception is critical in social interactions such as courtship, in both monochromatic and dichromatic species. In the Eared Dove (Zenaida auriculata), perhaps the most abundant South American Columbiforme, the plumage of males and females looks alike and both sexes share the same melanistic coloration with gray and pink tones. The aim of this study was therefore to determine whether evident sexual dichromatism exists in the plumage of the Eared Dove using a spectrophotometry technique in the avian-visible range (300–700 nm). The results of the classic colorimetric variables analysis (hue, chroma and brightness) show that males are in general brighter and have higher UV chroma values than females. The avian visual model points to differences in achromatic and chromatic levels between males and females in body regions possibly involved in sexual selection (e.g. the crown). The model also indicates chromatic or achromatic differences in body regions not subject to sexual selection such as the black spots on the wing coverts and white tail bands, both of which may be involved in intra- or inter-gender-specific communication.